In search of Hauptmann Strümpell: A case study of one man’s bibliographical legacy - Ladd, B (Vestiges: Traces of Record, 2021)
Kurt Strümpell, a German colonial officer in Cameroon at the beginning of the 20th century, wrote at least three scholarly articles on the culture, history, and languages of the Adamawa region, as well as a number of factual accounts of military operations by the German Schutztruppe. However, citations of these articles in subsequent literature give at least ten different forms of his name. Some of the different forms are plainly due to errors, but it also appears that in his one scholarly article published after the First World War (byline “F. Strümpell”) he used his second name, for reasons that are not clear. With the identity of “Kurt” and “F.” established, it is relatively straightforward to reconstruct an outline biography and to identify the more serious errors in the literature. These errors are relevant to current efforts to trace the provenance of colonial artefacts in European museums. Résumé: Kurt Strümpell, officier colonial allemand au Cameroun au début du 20e siècle, a écrit au moins trois articles savants sur la culture, l'histoire et les langues de la région d'Adamawa, ainsi qu'un certain nombre de récits factuels sur les opérations militaires de la Schutztruppe allemande. Cependant, les citations de ces articles dans la littérature ultérieure donnent au moins dix formes différentes de son nom. Certaines de ces formes différentes sont manifestement dues à des erreurs, mais il semble également que dans son seul article scientifique publié après la Première Guerre mondiale (sous la signature "F. Strümpell"), il ait utilisé son second nom, pour des raisons qui ne sont pas claires. L'identité de "Kurt" et de "F." étant établie, il est relativement simple de reconstituer les grandes lignes de la biographie et d'identifier les erreurs les plus graves dans la littérature. Ces erreurs sont pertinentes pour les efforts actuels visant à retracer la provenance des artefacts coloniaux dans les musées européens. Kurzfassung: Kurt Strümpell, ein deutscher Kolonialoffizier in Kamerun zu Beginn des 20. Jahrhunderts, schrieb mindestens drei wissenschaftliche Artikel über die Kultur, Geschichte und Sprachen der Adamaua-Region sowie eine Reihe von Tatsachenberichten über militärische Operationen der deutschen Schutztruppe. In der späteren Literatur warden diese Artikel jedoch mit mindestens zehn verschiedenen Formen seines Namens zitiert. Einige der verschiedenen Formen sind offensichtlich auf Irrtümer zurückzuführen, aber es scheint auch, dass er in seinem einzigen wissenschaftlichen Artikel aus der Nachkriegszeit, der unter dem Namen “F. Strümpell” erschien, aus unklaren Gründen seinen zweiten Namen verwendete. Nachdem die Identität von “Kurt” und “F.” feststeht, ist es relative einfach, eine grobe Biographie zu rekonstruieren und die schwerwiegenderen Fehler in der Literatur zu ermitteln. Diese Fehler sind für die aktuellen Bemühungen um die Rückverfolgung der Herkunft kolonialer Artefakte in europäischen Museen von Bedeutung.